2018
DOI: 10.1002/jcb.27643
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of protein kinase R protects against palmitic acid–induced inflammation, oxidative stress, and apoptosis through the JNK/NF‐kB/NLRP3 pathway in cultured H9C2 cardiomyocytes

Abstract: Background and Purpose: Double-stranded RNA-dependent protein kinase (PKR) is a critical regulator of apoptosis, oxidative stress, and inflammation under hyperlipidemic and insulin resistance conditions. Saturated free fatty acids, such as palmitic acid (PA), are known inducers of apoptosis in numerous cell types. However, the underlying molecular mechanism is not fully understood. The aim of the present study was to examine the effect of PA on cultured rat H9C2 cardiac myocytes cells and to investigate the PK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 71 publications
2
50
0
Order By: Relevance
“…We do not know if C16 blocks the activity of kinases that directly phosphorylate p53 on Ser46 and Ser392 or if it blocks the activity of a kinase, which phosphorylates p53 on other amino acid forming a signal for other kinases to modify Ser46 and Ser392. Some studies demonstrated that C16 protects against tissue damage and inflammation, especially in the central nervous system [36,50,51]. In light of our observation that C16 inhibits p53 activation and the fact that p53 is strong inducer of cell death, it must be considered that some cytoprotective activities of this compound are mediated through the inhibition of p53-induced apoptosis or inflammation.…”
Section: Discussionmentioning
confidence: 88%
“…We do not know if C16 blocks the activity of kinases that directly phosphorylate p53 on Ser46 and Ser392 or if it blocks the activity of a kinase, which phosphorylates p53 on other amino acid forming a signal for other kinases to modify Ser46 and Ser392. Some studies demonstrated that C16 protects against tissue damage and inflammation, especially in the central nervous system [36,50,51]. In light of our observation that C16 inhibits p53 activation and the fact that p53 is strong inducer of cell death, it must be considered that some cytoprotective activities of this compound are mediated through the inhibition of p53-induced apoptosis or inflammation.…”
Section: Discussionmentioning
confidence: 88%
“…For example, exposure of myotubes to palmitic acid leads to attenuated insulin signaling, but exposure to oleic acid does not cause these changes; in addition, co‐incubation of palmitic acid–exposed cells with a lower concentration of oleic acid reverses the effects of the latter . In our in vitro study, we used palmitate to induce insulin resistance, which is a classic insulin resistance model that has been used in many studies . Although we did not determine whether stearate and oleate have the same effects on mitochondria in our experiment, it would be interesting and worth further investigation.…”
Section: Discussionmentioning
confidence: 94%
“…Inflammation induced by obesity activates JNK and NF-κB signaling pathways in insulin target cells, which plays a key role in insulin resistance. 41,42 At the cellular level, Inflammation induced by obesity may be involved in phosphorylation of the transcription factor NF-κB leading to an increase of the expression of TNFα and IL-6 genes associated with insulin resistance. 43 Inflammatory cytokines may inhibit IRS-1 Tyr phosphorylation in the insulin signaling pathway, also lead to increase in JNK phosphorylation, and decrease Akt phosphorylation.…”
Section: Jnk Signaling Pathway and Nf-κb Signaling Pathwaymentioning
confidence: 99%